PERBEDAAN INFORMASI CITRA SEKUEN THICK-SLAB SINGLE-SHOT FAST SPIN ECHO (SS-FSE) DAN SEKUEN 3D-FAST SPIN ECHO (FSE) PADA PEMERIKSAAN MAGNETIC RESONANCE CHOLANGIOPANCREATICOGRAPHY (MRCP) - Anisa Nur Istiqomah; Hermina Sukmaningtyas; Luthfi Rusyadi (JRI (Jurnal Radiografer Indonesia), 2018)
Backgroud:There are sequences that have the same image and assessment functions are sequences thick-slab SS- FSE and 3D-FSE. Each hospital uses a different sequences for MRCP examination. Based on the different uses of these sequences carried out research with the aim to determine differences in image information thick-slab SS- FSE and 3D-FSE sequences and also to see better sequence for MRCP examination. Methods: Type of this research is quantitative with observation approach. Ten patient have diagnose system biliaris and pancreas disease undergo MRCP with thick-slab SS-FSE and 3D-FSE sequence. Assessment images information using questionnaire that were read by three radiologist. Inter observer agreement examined by Cohen’s Kappa test. Analysis to discover the different of anatomy information, conspicuity of lesion, and artifact using cross tabulation and Wilcoxon test. To discover better sequence observe the mean rank of wilcoxon test. Results: Result of this research demonstrate that there’s significantly different between sequence thick-slab SSFSE and 3D-FSE toward anatomy information p=0,010; conspicuity of lesion p=0,013; artifact p=0,008; Cystic Duct p=0,157; intra hepatic duct p=0,405. Conclusion:There are significant image informationdifferences of Thick-slab SS-FSE and 3D-FSE sequences in MRCP examination.Better sequence for MRCP examination is thick-slab SS-FSE because short acquisition time and less artifact also showing conspicuity of lesion clearly. Sequence 3D-FSE still used to see small ductus as intra hepatic duct.